A flexible high temperature resistant BT resin based copper clad laminate and preparation method thereof
By performing micro-etching and silane coupling modification treatment on the copper foil and modifying the BT resin to generate a branched network structure, the problem of poor adhesion of flexible copper clad plates at high temperatures is solved, and higher high temperature resistance and stability are achieved.
Patent Information
- Application Number
- CN202410867607.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-01
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-07-01
AI Technical Summary
The existing flexible copper clad plate has poor adhesion at high temperatures, resulting in curling of the substrate film, decreasing the peeling strength of the copper foil and decreasing the dielectric performance, affecting the transmission of electrical signals.
By undergoing micro-etching and silane coupling modification treatment on the copper foil, the adhesion of the BT resin is enhanced, and the modified BT resin with branched network structure is generated by reaction of modified melamine and bismaleimide prepolymer, which improves its mechanical properties and thermal stability.
The adhesion between BT resin and copper foil is significantly improved, the high temperature resistance of copper clad plate is enhanced, the layering of the resin layer and copper foil is avoided, and the stability of electrical signal transmission is ensured.
Smart Images

Figure BDA0004920665240000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper clad laminates, and in particular to a flexible high temperature resistant BT resin based copper clad laminate and a preparation method thereof. Background Art
[0002] With the rapid development of the electronic equipment industry, more and more electronic devices have appeared in people's lives and become indispensable necessities in life, such as smart phones, tablets, smart watches, etc. In order to make people's lives more convenient and win people's love, these electronic devices are also increasingly pursuing lightness, portability, multi-functions, and high frequency.
[0003] As the substrate of printed circuit boards, copper clad laminates are important components for connecting and supporting electronic components. Depending on the different base materials in copper clad laminates, they can usually be divided into rigid copper clad laminates that are not easy to bend and flexible copper clad laminates that can be bent. Among them, a more prominent advantage of flexible copper clad laminates is that they can reduce the size and weight of the equipment. Therefore, in the context of today's era, as electronic devices are developing towards being light, portable, multifunctional, and high-frequency, people's demand for flexible copper clad laminates will become greater and greater.
[0004] At present, the market mainly uses polyimide (PI), polyester (PET) and polynaphthyl ester (PEN) as resin substrates in flexible copper clad laminates. However, PET and PEN have poor heat resistance, and PI has a high water absorption rate. These shortcomings will cause the substrate film to curl and the peel strength of the copper foil to decrease. At the same time, it will also cause the dielectric properties to decrease, which will eventually affect the transmission of electrical signals. BT resin is a thermosetting resin with good heat resistance, low dielectric loss and good insulation performance. It is an excellent material for high-frequency transmission circuit boards, but the viscosity of BT resin is too low, and it will delaminate with the copper foil at high temperatures.
[0005] Therefore, it is extremely necessary to obtain a high-temperature resistant BT resin-based copper clad laminate. In the scheme, the copper foil is modified and a modified BT resin is prepared. While enhancing the high-temperature resistance of the BT resin itself, the adhesion between the two is enhanced to obtain a more flexible copper clad laminate that meets the requirements. Summary of the invention
[0006] The object of the present invention is to provide a flexible high temperature resistant BT resin based copper clad laminate and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0008] Provided is a flexible high temperature resistant BT resin based copper clad laminate having a three-layer structure, which comprises, from top to bottom, a modified copper foil layer, a BT resin layer, and a modified copper foil layer; a side of the modified copper foil layer contacting the BT resin layer is modified;
[0009] The BT resin layer comprises the following raw materials by weight: 60 to 80 parts of modified BT resin, 15 to 30 parts of modified filler; 25 to 45 parts of epoxy resin, and 15 to 25 parts of polyphenylene ether resin;
[0010] The modified copper foil layer has a thickness of 10 to 50 μm, and the BT resin layer has a thickness of 100 μm.
[0011] Furthermore, the method for preparing the flexible high temperature resistant BT resin-based copper clad laminate comprises the following steps:
[0012] Step 1: roughening the side of the copper foil in contact with the resin, and then modifying the side with a bismaleimide-grafted mercaptosilane coupling agent to obtain a modified copper foil;
[0013] Step 2: modifying the filler with a bismaleimide-grafted mercaptosilane coupling agent to obtain a modified filler;
[0014] Step 3: (1) reacting hexachlorocyclotriphosphazene with melamine to obtain modified melamine;
[0015] (2) reacting modified melamine with N-(3-chloro-2-methylphenyl)maleimide to obtain melamine having an amide group;
[0016] (3) reacting melamine having an amide group with bismaleimide to obtain a modified bismaleimide prepolymer;
[0017] (4) reacting the modified bismaleimide prepolymer with cyanate to obtain a modified BT resin;
[0018] Step 4: Add the modified BT resin, modified filler, epoxy resin and polyphenylene ether resin into a mixer, mix and stir at 120-130° C. for 30-60 minutes, and extrude and mold at 105-115° C. to obtain a BT resin layer;
[0019] Step 5: stack the modified copper foil, BT resin layer, and modified copper foil in sequence, place them in a vacuum hot press, and wait for them to solidify to obtain a flexible high-temperature resistant BT resin-based copper clad laminate.
[0020] Furthermore, the treatment method of the modified copper foil is as follows: (1) the micro-etching liquid is evenly applied to the side of the copper foil contacting the resin, and after micro-etching for 1 to 3 seconds, it is cleaned with water flow, and the micro-etched surface of the copper foil is blown dry with an air gun to obtain a roughened copper foil; (2) an anhydrous ethanol solution of bismaleimide grafted mercaptosilane coupling agent is evenly applied to the micro-etched surface of the roughened copper foil, and after 5 to 10 minutes, the surface is blown dry with an air gun to obtain a silane coupling agent modified copper foil; (3) the silane coupling agent modified copper foil is placed at 100 to 110° C., baked for 1 to 3 hours, and after it is naturally cooled to room temperature, it is washed 2 to 3 times with an ethanol solution to obtain a modified copper foil.
[0021] Furthermore, the micro-etching liquid model is RTL-413B, purchased from Shanghai Ruiteliang Chemical Co., Ltd.; the coating amount is 0.1-0.3 mL / cm 3 .
[0022] Furthermore, the concentration of the anhydrous ethanol solution of the bismaleimide grafted mercaptosilane coupling agent is 2-3 wt %, and the coating amount is 0.2-0.5 mL / cm 3 .
[0023] Furthermore, the preparation method of the bismaleimide grafted mercaptosilane coupling agent is: disperse 4,4'-methylenebis(N-phenylmaleimide), a photoinitiator, and a mercaptosilane coupling agent in anhydrous ethanol, ultrasonically disperse for 5 to 15 minutes, irradiate with 365nm ultraviolet light for 30 to 60 minutes, heat to 75 to 80°C, evaporate and remove ethanol, and obtain a bismaleimide grafted mercaptosilane coupling agent.
[0024] Furthermore, the mass ratio of the 4,4'-methylenebis(N-phenylmaleimide), mercaptosilane coupling agent and photoinitiator is (0.1-0.3):5:(0.01-0.05).
[0025] Furthermore, the mercaptosilane coupling agent includes but is not limited to any one of γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane.
[0026] Furthermore, the modification method of the modified filler is: adding nano-silica to an anhydrous solution of bismaleimide-grafted mercaptosilane coupling agent, ultrasonically treating at 40-60° C. for 60-120 min, filtering and drying to obtain the modified filler.
[0027] Furthermore, the mass ratio of the nano-silica to the bismaleimide-grafted mercaptosilane coupling agent is 50:1.
[0028] Furthermore, the preparation method of the modified BT resin is as follows: (1) adding melamine to pyridine and stirring to dissolve it to obtain a melamine solution; adding hexachlorocyclotriphosphazene to pyridine and stirring to dissolve it to obtain a hexachlorocyclotriphosphazene solution; (2) heating the melamine solution to 100-140° C., stirring, adding the hexachlorocyclotriphosphazene solution thereto, maintaining the reaction temperature, reflux reaction for 12-24 hours, ending the reaction, and after the reaction system is naturally cooled to room temperature, filtering, washing, and drying to obtain modified melamine; (3) dissolving the modified melamine in pyridine, adjusting the solution temperature to 100-140° C., stirring, and dropping N-(3-chloro-2-pyridine) into the solution; (4) adding melamine with an amide group into a tetrahydrofuran solution, stirring to dissolve it, and then adding bismaleimide to the solution, stirring and reacting at 130-145° C. for 1-2 hours to obtain a modified bismaleimide prepolymer; (5) adding cyanate to the modified bismaleimide prepolymer, and refluxing at 110-140° C. for 1-3 hours to terminate the reaction. After the reaction system is naturally cooled to room temperature, filtering, washing, and drying are performed to obtain a modified BT resin.
[0029] Furthermore, the mass ratio of melamine to hexachlorocyclotriphosphazene is 1:2.
[0030] Furthermore, the mass ratio of the modified melamine to N-(3-chloro-2-methylphenyl)maleimide is 1:(3-5).
[0031] Furthermore, the mass ratio of the melamine having an amide group, bismaleimide, cyanate ester and tetrahydrofuran is (1-2):40:40:100.
[0032] Furthermore, the bismaleimide includes but is not limited to any one of 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4,4'-diaminodiphenylmethane bismaleimide, and 4,4'-diaminodiphenyl ether bismaleimide.
[0033] Furthermore, the cyanate ester includes but is not limited to any one of bisphenol A cyanate ester resin and bisphenol E cyanate ester resin.
[0034] Furthermore, the hot pressing process parameters are set as follows: hot pressing pressure 1-3 MPa, hot pressing temperature 160-210° C., and hot pressing time 15-30 min.
[0035] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention performs micro-etching and coupling modification treatment on the copper foil, so that the BT resin layer and the copper foil layer can be more firmly bonded, and the disadvantage of poor adhesion of the BT resin is solved, thereby enhancing the performance of the copper clad laminate and improving the high temperature resistance of the copper clad laminate; and the coupling agent is modified with bismaleimide, which further promotes the bonding of the copper foil and the BT resin layer; the BT resin is further modified in the scheme, and modified melamine with a branched network structure is generated by reaction, which acts as a rigid particle to enhance the performance of the BT resin. After the improvement, the mechanical properties and thermal stability of the BT resin are enhanced; at the same time, under the action of epoxy resin, polyphenylene ether resin and modified filler, the adhesion of the BT resin is further enhanced; and finally a high temperature resistant BT resin-based copper clad laminate with stable performance is prepared.
[0036] (1) Since the adhesion of BT resin to copper foil is poor at high temperature, in order to improve it, the copper foil is micro-etched and modified with silane coupling agent in the scheme; the micro-etching can cause microscopic defects on the side of the copper foil that contacts the BT resin, and the silane coupling agent can enter these microscopic pores, so that the copper foil and the BT resin can form a more solid anchoring structure; combined with the heat treatment technology, the coupling agent can be more firmly combined with the copper foil, and finally the purpose of enhancing the adhesion between the BT resin and the copper foil is achieved, so that the BT resin layer is not easy to delaminate from the copper foil, thereby ensuring the performance of the copper clad laminate; in the scheme, a bismaleimide-grafted mercaptosilane coupling agent is further prepared to modify the copper foil, and the coupling agent improves the compatibility of the copper foil and the BT resin layer, and can also improve the adhesion of the two to a certain extent; that is, in this step, the performance of the copper clad laminate is stabilized by improving the adhesion between the resin layer and the copper foil layer, that is, the prepared copper clad laminate has better high temperature resistance.
[0037] (2) Filler is an important material for improving the high temperature resistance of resin. In the scheme, nano-silica is used as an inorganic filler and modified with bismaleimide-grafted mercaptosilane coupling agent, which promotes the compatibility of inorganic particles in the resin and improves the high temperature resistance of BT resin.
[0038] In the scheme (3), the hydrogen on the amino group of melamine replaces the chlorine on the hexachlorocyclotriphosphazene, and then the two are grafted to obtain modified melamine, which is then reacted with N-(3-chloro-2-methylphenyl)maleimide to amidate the amino group on the modified melamine, and then grafted with bismaleimide to form a prepolymer, and finally a modified BT resin is obtained. The reaction of melamine and hexachlorocyclotriphosphazene will form a microspherical structure. The existence of this branched network structure can be used as a rigid particle to strengthen the network structure of the resin, which can enhance the performance of the BT resin; at the same time, the surface of the branched network structure is amidated to improve the compatibility with bismaleimide, making the branched network structure more stable, and thus the obtained BT resin has better performance; the prepared modified BT resin will form a stable triazine ring structure during the curing process, and the heat resistance of the BT resin will be further improved; in addition, the stability of the branched network structure can also improve the thermal stability of the BT resin to a certain extent. DETAILED DESCRIPTION
[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] It should be noted that the purchasers of all raw materials involved in the present invention include, without any special restrictions, the following examples:
[0041] RTL-413B microetching solution (Shanghai Ruiteliang Chemical Co., Ltd.); 4,4'-methylenebis(N-phenylmaleimide) purity 99% (Hubei Qifei Pharmaceutical Chemical Co., Ltd.); photoinitiator purity 99%, model IHT-PI (Hubei Qifei Pharmaceutical Chemical Co., Ltd.); γ-mercaptopropyltrimethoxysilane purity 99% (Hubei Yongkuo Technology Co., Ltd.); nano-silicon dioxide purity 99%, particle size 2-5μm ((Alpha) Zhengzhou Huiju Chemical Co., Ltd.); melamine purity 99% (Hubei Yongkuo Technology Co., Ltd.); hexachlorocyclotriphosphazene purity 99% (Shanghai Yuanye Biotechnology Co., Ltd.); N-(3-chloro-2-methylphenyl)maleimide purity is 96% (Custom Chemicals, USA); 4,4-diaminodiphenylmethane bismaleimide purity is 96% (TCI (Shanghai) Chemical Industry Development Co., Ltd.); bisphenol A cyanate resin purity is 99%, item number: 001 (Xinyi Yongcheng Chemical Co., Ltd.); bisphenol A epoxy resin purity is 99%, model: E-03 (Hubei Xinhongli Chemical Co., Ltd.); polyphenylene ether resin model PX9406-701 (Dongguan Dongshuo Plastic Raw Materials Co., Ltd.).
[0042] Preparation of bismaleimide grafted mercaptosilane coupling agent: 0.9 parts of 4,4'-methylenebis(N-phenylmaleimide), 0.09 parts of photoinitiator, and 15 parts of γ-mercaptopropyltrimethoxysilane are dispersed in 50 parts of anhydrous ethanol, and after ultrasonic dispersion for 10 minutes, irradiated with 365nm ultraviolet light for 60 minutes, heated to 78°C, and evaporated to remove ethanol to obtain a bismaleimide grafted mercaptosilane coupling agent.
[0043] Example 1: A method for preparing a flexible high temperature resistant BT resin based copper clad laminate:
[0044] Step 1: Treatment of modified copper foil: (1) Take two pieces of 25μm copper foil and evenly apply RTL-413B micro-etching liquid on the side that contacts the resin. The coating amount is 0.2mL / cm 3 After micro-etching for 2 seconds, clean it with water and blow dry the micro-etched surface of the copper foil with an air gun to obtain a roughened copper foil; (2) evenly apply a 2 wt % bismaleimide grafted mercaptosilane coupling agent anhydrous ethanol solution to the micro-etched surface of the roughened copper foil, with a coating amount of 0.4 mL / cm 3 After 10 minutes, the surface was dried with an air gun to obtain a silane coupling agent modified copper foil; (3) the silane coupling agent modified copper foil was placed at 105° C. and baked for 2 hours. After it was naturally cooled to room temperature, it was washed with an ethanol solution for 3 times to obtain a modified copper foil;
[0045] Step 2: Preparation of modified filler: Add 30 parts of nano-silica to 30 parts of 2 wt% bismaleimide grafted mercaptosilane coupling agent anhydrous ethanol solution, ultrasonically treat at 50° C. for 80 min, filter and dry to obtain modified filler;
[0046] Step 3: Preparation of modified BT resin: (1) Add 1 part of melamine to 20 parts of pyridine, stir to dissolve it, and obtain a melamine solution; add 2 parts of hexachlorocyclotriphosphazene to 20 parts of pyridine, stir to dissolve it, and obtain a hexachlorocyclotriphosphazene solution; (2) Heat the melamine solution to 120°C, add the hexachlorocyclotriphosphazene solution thereto while stirring, maintain the reaction temperature, reflux for 24 hours, terminate the reaction, wait for the reaction system to cool naturally to room temperature, filter, wash, and dry to obtain modified melamine; (3) Dissolve 1 part of modified melamine in pyridine, adjust the solution temperature to 130°C, and drop 4 parts of N-(3-chloro-2-methylphenyl)maleimide into the solution while stirring. After the addition is completed, reflux reaction for 24 hours to terminate the reaction. After the reaction system is naturally cooled to room temperature, it is filtered, washed and dried to obtain melamine with an amide group; (4) 1.6 parts of melamine with an amide group are added to 100 parts of tetrahydrofuran solution, stirred to dissolve, and then 40 parts of 4,4-diaminodiphenylmethane bismaleimide are added to the solution, stirred and reacted at 135°C for 2 hours to obtain a modified bismaleimide prepolymer; (5) 40 parts of bisphenol A type cyanate resin are added to the modified bismaleimide prepolymer, reflux reaction is carried out at 130°C for 2 hours to terminate the reaction. After the reaction system is naturally cooled to room temperature, it is filtered, washed and dried to obtain a modified BT resin;
[0047] Step 4: Add 75 parts of modified BT resin, 22 parts of modified filler, 35 parts of E-03 bisphenol A epoxy resin, and 20 parts of PX9406-701 polyphenylene ether resin into a mixer, mix and stir at 125° C. for 60 minutes, and extrude and mold at 110° C. to obtain a BT resin layer with a thickness of 100 μm;
[0048] Step 5: stack the modified copper foil, BT resin layer, and modified copper foil in sequence, place them in a vacuum hot press for hot pressing, set the parameters: hot pressing pressure 3Mpa, hot pressing temperature 200℃, hot pressing time 20min, wait for it to solidify, and obtain a 145μm thick flexible high temperature resistant BT resin-based copper clad laminate.
[0049] Example 2: A method for preparing a flexible high temperature resistant BT resin based copper clad laminate:
[0050] Step 1: Treatment of modified copper foil: (1) Take two pieces of 25μm copper foil and evenly apply RTL-413B micro-etching liquid on the side that contacts the resin. The coating amount is 0.1mL / cm 3 After micro-etching for 1 second, clean it with water and blow dry the micro-etched surface of the copper foil with an air gun to obtain a roughened copper foil; (2) evenly apply a 2 wt % bismaleimide grafted mercaptosilane coupling agent anhydrous ethanol solution to the micro-etched surface of the roughened copper foil, with a coating amount of 0.2 mL / cm 3After 5 minutes, the surface was dried with an air gun to obtain a silane coupling agent modified copper foil; (3) the silane coupling agent modified copper foil was placed at 105° C. and baked for 1 hour. After it was naturally cooled to room temperature, it was washed twice with an ethanol solution to obtain a modified copper foil;
[0051] Step 2: Preparation of modified filler: Add 30 parts of nano-silica to 30 parts of 2 wt% bismaleimide grafted mercaptosilane coupling agent anhydrous ethanol solution, ultrasonically treat at 50° C. for 80 min, filter and dry to obtain modified filler;
[0052] Step 3: Preparation of modified BT resin: (1) Add 1 part of melamine to 20 parts of pyridine, stir to dissolve it, and obtain a melamine solution; add 2 parts of hexachlorocyclotriphosphazene to 20 parts of pyridine, stir to dissolve it, and obtain a hexachlorocyclotriphosphazene solution; (2) Heat the melamine solution to 120°C, stir, add the hexachlorocyclotriphosphazene solution thereto, maintain the reaction temperature, reflux for 24 hours, terminate the reaction, wait for the reaction system to cool naturally to room temperature, filter, wash, and dry to obtain modified melamine; (3) Dissolve 1 part of modified melamine in pyridine, adjust the solution temperature to 130°C, and stir, dropwise add 3 parts of N-(3-chloro-2-methylphenyl)maleimide to the solution. (4) adding 1 part of melamine with an amide group to 100 parts of tetrahydrofuran solution, stirring to dissolve it, and then adding 40 parts of 4,4'-diaminodiphenylmethane bismaleimide to the solution, stirring and reacting at 135°C for 2 hours to obtain a modified bismaleimide prepolymer; (5) adding 40 parts of bisphenol A cyanate resin to the modified bismaleimide prepolymer, and refluxing at 130°C for 2 hours to terminate the reaction. After the reaction system is naturally cooled to room temperature, filtering, washing and drying are performed to obtain a modified BT resin;
[0053] Step 4: Add 75 parts of modified BT resin, 22 parts of modified filler, 35 parts of E-03 bisphenol A epoxy resin, and 20 parts of PX9406-701 polyphenylene ether resin into a mixer, mix and stir at 125° C. for 60 minutes, and extrude and mold at 110° C. to obtain a BT resin layer with a thickness of 100 μm;
[0054] Step 5: stack the modified copper foil, BT resin layer, and modified copper foil in sequence, place them in a vacuum hot press for hot pressing, set the parameters: hot pressing pressure 3Mpa, hot pressing temperature 200℃, hot pressing time 20min, wait for it to solidify, and obtain a 145μm thick flexible high temperature resistant BT resin-based copper clad laminate.
[0055] Embodiment 3: A method for preparing a flexible high temperature resistant BT resin based copper clad laminate:
[0056] Step 1: Treatment of modified copper foil: (1) Take two pieces of 25μm copper foil and evenly apply RTL-413B micro-etching liquid on the side that contacts the resin. The coating amount is 0.3mL / cm 3 After micro-etching for 3 seconds, clean it with water and blow dry the micro-etched surface of the copper foil with an air gun to obtain a roughened copper foil; (2) evenly apply a 2 wt % bismaleimide grafted mercaptosilane coupling agent anhydrous ethanol solution to the micro-etched surface of the roughened copper foil, with a coating amount of 0.5 mL / cm 3 After 10 minutes, the surface was dried with an air gun to obtain a silane coupling agent modified copper foil; (3) the silane coupling agent modified copper foil was placed at 105° C. and baked for 3 hours. After it was naturally cooled to room temperature, it was washed with an ethanol solution for 3 times to obtain a modified copper foil;
[0057] Step 2: Preparation of modified filler: Add 30 parts of nano-silica to 30 parts of 2 wt% bismaleimide grafted mercaptosilane coupling agent anhydrous ethanol solution, ultrasonically treat at 50° C. for 80 min, filter and dry to obtain modified filler;
[0058] Step 3: Preparation of modified BT resin: (1) Add 1 part of melamine to 20 parts of pyridine, stir to dissolve it, and obtain a melamine solution; add 2 parts of hexachlorocyclotriphosphazene to 20 parts of pyridine, stir to dissolve it, and obtain a hexachlorocyclotriphosphazene solution; (2) Heat the melamine solution to 120°C, stir, add the hexachlorocyclotriphosphazene solution thereto, maintain the reaction temperature, reflux for 24 hours, terminate the reaction, wait for the reaction system to cool naturally to room temperature, filter, wash, and dry to obtain modified melamine; (3) Dissolve 1 part of modified melamine in pyridine, adjust the solution temperature to 130°C, stir, and drop 5 parts of N-(3-chloro-2-methylphenyl)maleimide into the solution. (4) adding 2 parts of melamine with amide group to 100 parts of tetrahydrofuran solution, stirring to dissolve it, adding 40 parts of 4,4'-diaminodiphenylmethane bismaleimide to the solution, stirring and reacting at 135°C for 2 hours to obtain modified bismaleimide prepolymer; (5) adding 40 parts of bisphenol A cyanate resin to the modified bismaleimide prepolymer, refluxing at 130°C for 2 hours to terminate the reaction, and after the reaction system is naturally cooled to room temperature, filtering, washing and drying to obtain modified BT resin;
[0059] Step 4: Add 75 parts of modified BT resin, 22 parts of modified filler, 35 parts of E-03 bisphenol A epoxy resin, and 20 parts of PX9406-701 polyphenylene ether resin into a mixer, mix and stir at 125° C. for 60 minutes, and extrude and mold at 110° C. to obtain a BT resin layer with a thickness of 100 μm;
[0060] Step 5: stack the modified copper foil, BT resin layer, and modified copper foil in sequence, place them in a vacuum hot press for hot pressing, set the parameters: hot pressing pressure 3Mpa, hot pressing temperature 200℃, hot pressing time 20min, wait for it to solidify, and obtain a 145μm thick flexible high temperature resistant BT resin-based copper clad laminate.
[0061] Comparative Example 1: Taking Example 1 as a control, Comparative Example 1 is adjusted as follows: the copper foil is only subjected to micro-etching treatment, and no coupling modification is performed, and the other processes remain unchanged, specifically:
[0062] Step 1: Treatment of modified copper foil: (1) Take two pieces of copper foil and evenly apply RTL-413B micro-etching liquid on the side that contacts the resin. The coating amount is 0.2mL / cm 3 After micro-etching for 2 seconds, clean it with water flow and blow dry the micro-etched surface of the copper foil with an air gun to obtain a roughened copper foil.
[0063] Comparative Example 2: Taking Example 1 as a control, Comparative Example 2 is adjusted as follows: the copper foil is not treated, and the other processes remain unchanged.
[0064] Comparative Example 3: Taking Example 1 as a control, Comparative Example 3 is adjusted as follows: bismaleimide is not modified, and the other processes remain unchanged, specifically:
[0065] Step 2: Add 40 parts of 4,4'-diaminodiphenylmethane bismaleimide to 40 parts of bisphenol A cyanate resin, reflux at 130°C for 2 hours to terminate the reaction, and after the reaction system is naturally cooled to room temperature, filter, wash and dry to obtain a modified BT resin.
[0066] Comparative Example 4: Taking Example 1 as a control, Comparative Example 4 is adjusted as follows: the modified melamine is not amidated, and the other processes remain unchanged, specifically: Step 2: (4) 1.6 parts of modified melamine are added to 100 parts of tetrahydrofuran solution, stirred to dissolve, and then 40 parts of 4,4'-diaminodiphenylmethane bismaleimide are added to the solution, and the reaction is stirred at 135°C for 2h to obtain a modified bismaleimide prepolymer.
[0067] According to the testing method of IPC-TM-650, the peeling performance test was performed on the flexible high temperature resistant BT resin based copper clad laminates prepared in Examples 1 to 3 and Comparative Examples 1 to 4.
[0068] Testing experiment: (1) At 25° C., the peel strength of the copper clad laminates prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was tested using a tensile testing machine;
[0069] (2) The copper clad laminates prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were placed in an air-type high temperature box and heated to 150° C., and their peel strength was tested using a tensile testing machine; the specific data are shown in Table 1:
[0070] Table 1
[0071]
[0072] Result analysis: According to the data analysis of Table 1 above, it can be seen that the present invention effectively improves the adhesion of the two by preparing modified BT resin and modifying the copper foil; at high temperatures, the resin layer and the copper foil layer still have good adhesion, that is, the present invention prepares a BT resin-based copper clad laminate with excellent high temperature resistance.
[0073] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A flexible high temperature resistant BT resin based copper clad laminate, characterized in that: The copper clad laminate has a three-layer structure, which includes, from top to bottom, a modified copper foil layer, a BT resin layer, and a modified copper foil layer; a side of the modified copper foil layer contacting the BT resin layer is modified; The BT resin layer comprises the following raw materials by weight: 60 to 80 parts of modified BT resin, 15 to 30 parts of modified filler; 25 to 45 parts of epoxy resin, and 15 to 25 parts of polyphenylene ether resin; The modified copper foil layer has a thickness of 10 to 50 μm, and the BT resin layer has a thickness of 100 μm; The preparation method of the modified BT resin is: (1) adding melamine to pyridine and stirring to dissolve it to obtain a melamine solution; adding hexachlorocyclotriphosphazene to pyridine and stirring to dissolve it to obtain a hexachlorocyclotriphosphazene solution; (2) heating the melamine solution to 100-140° C., adding the hexachlorocyclotriphosphazene solution thereto under stirring, maintaining the reaction temperature, and reflux reacting for 12-24 hours, then terminating the reaction, and after the reaction system is naturally cooled to room temperature, filtering, washing, and drying to obtain modified melamine; (3) Dissolving the modified melamine in pyridine, adjusting the solution temperature to 100-140° C., adding N-(3-chloro-2-methylphenyl)maleimide dropwise to the solution under stirring, and after the addition is complete, reflux reaction for 24 hours to terminate the reaction, and after the reaction system is naturally cooled to room temperature, filtering, washing, and drying to obtain melamine with an amide group; (4) adding melamine having an amide group to a tetrahydrofuran solution, stirring to dissolve it, then adding bismaleimide to the solution, stirring and reacting at 130 to 145° C. for 1 to 2 hours to obtain a modified bismaleimide prepolymer; (5) adding cyanate to the modified bismaleimide prepolymer, and performing reflux reaction at 110 to 140° C. for 1 to 3 hours to terminate the reaction, and after the reaction system is naturally cooled to room temperature, filtering, washing, and drying to obtain a modified BT resin; The mass ratio of melamine to hexachlorocyclotriphosphazene is 1:2; the mass ratio of modified melamine to N-(3-chloro-2-methylphenyl)maleimide is 1:(3-5); the mass ratio of melamine having an amide group, bismaleimide, cyanate ester and tetrahydrofuran is (1-2):40:40:
100.
2. The method for preparing a flexible high temperature resistant BT resin based copper clad laminate according to claim 1, characterized in that: The following steps are involved: Step 1: roughening the side of the copper foil in contact with the resin, and then modifying the side with a bismaleimide-grafted mercaptosilane coupling agent to obtain a modified copper foil; Step 2: modifying the filler with a bismaleimide-grafted mercaptosilane coupling agent to obtain a modified filler; Step 3: (1) reacting hexachlorocyclotriphosphazene with melamine to obtain modified melamine; (2) reacting the modified melamine with N-(3-chloro-2-methylphenyl)maleimide to obtain melamine having an amide group; (3) reacting the melamine having an amide group with bismaleimide to obtain a modified bismaleimide prepolymer; (4) reacting the modified bismaleimide prepolymer with cyanate to obtain a modified BT resin; Step 4: Add the modified BT resin, modified filler, epoxy resin and polyphenylene ether resin into a mixer, mix and stir at 120-130° C. for 30-60 minutes, and extrude and mold at 105-115° C. to obtain a BT resin layer; Step 5: stack the modified copper foil, BT resin layer, and modified copper foil in sequence, place them in a vacuum hot press, and wait for them to solidify to obtain a flexible high-temperature resistant BT resin-based copper clad laminate.
3. The method for preparing a flexible high temperature resistant BT resin based copper clad laminate according to claim 2, characterized in that: The processing method of the modified copper foil is: (1) Apply micro-etching liquid evenly on the side of the copper foil that contacts the resin. After micro-etching for 1 to 3 seconds, clean it with water flow and blow dry the micro-etched surface of the copper foil with an air gun to obtain a roughened copper foil; (2) evenly coating the anhydrous ethanol solution of bismaleimide grafted mercaptosilane coupling agent on the roughened micro-etched surface of the copper foil, and drying the surface with an air gun after 5 to 10 minutes to obtain a silane coupling agent modified copper foil; (3) placing the silane coupling agent modified copper foil at 100-110° C. for 1-3 hours, allowing it to cool naturally to room temperature, and then washing it with an ethanol solution for 2-3 times to obtain a modified copper foil.
4. The method for preparing a flexible high temperature resistant BT resin based copper clad laminate according to claim 3, characterized in that: The preparation method of the bismaleimide grafted mercaptosilane coupling agent is as follows: 4,4'-methylenebis(N-phenylmaleimide), a photoinitiator and a mercaptosilane coupling agent are dispersed in anhydrous ethanol, ultrasonically dispersed for 5 to 15 minutes, irradiated with 365nm ultraviolet light for reaction for 30 to 60 minutes, heated to 75 to 80°C, evaporated and removed the ethanol, and obtained the bismaleimide grafted mercaptosilane coupling agent.
5. The method for preparing a flexible high temperature resistant BT resin based copper clad laminate according to claim 4, characterized in that: The mass ratio of the 4,4'-methylenebis(N-phenylmaleimide), mercaptosilane coupling agent and photoinitiator is (0.1-0.3):5:(0.01-0.05).
6. The method for preparing a flexible high temperature resistant BT resin based copper clad laminate according to claim 3, characterized in that: The micro-etching liquid coating amount is 0.1-0.3 mL / cm 3 The concentration of the anhydrous ethanol solution of bismaleimide grafted mercaptosilane coupling agent is 2-3wt%, and the coating amount is 0.2-0.5mL / cm 3 .
7. The method for preparing a flexible high temperature resistant BT resin based copper clad laminate according to claim 2, characterized in that: The modified filler is modified by adding nano silicon dioxide into an anhydrous ethanol solution of a bismaleimide-grafted mercaptosilane coupling agent, ultrasonically treating the solution for 60 to 120 minutes at 40 to 60° C., filtering the solution, and drying the solution to obtain the modified filler.
8. The method for preparing a flexible high temperature resistant BT resin based copper clad laminate according to claim 2, characterized in that: The hot pressing process parameters are set as follows: hot pressing pressure 1-3 MPa, hot pressing temperature 160-210° C., and hot pressing time 15-30 min.
Citation Information
Patent Citations
Double copper-coated surface base material structure for LED flexible strip and manufacturing method thereof
CN102744934A
Thermosetting resin composition and method for manufacturing prepreg and laminated board by using thermosetting resin composition
CN103937156A
Preparation method of environment-friendly adhesive for board
CN107987765A
Modified BT resin and preparation method thereof
CN115873406A
Treated copper foil and circuit board
CN1657279A